Inversion of Bubble Size Distribution Based on Whale Optimization Algorithm - Zhenzhong Lu; Ziqi Hu; Lin Ma; Shangtao Huang; Tao Peng; Min Liu; Biao Han; Jiali Liao; Zihao Wang; Yanling Sun (IEEE Photonics Journal, 2024)
A particle size inversion method based on whale optimization algorithm (WOA) is presented. In the experiment, the small angle forward scattering measurement system is used to conduct experimental research on the inversion of bubble particle size. WOA is used to invert and simulate the bubbles that follow a certain distribution, adding different levels of random noise to verify the stability of the algorithm. The results verify the feasibility and stability of applying WOA to particle size inversion.